ANALYSIS OF EFFICACY OF KALINGADI TAILA NASYA IN THE APEENASA MANAGEMENT - Prem, Pradeep Kumar; Pandey, Kumari Uma; Mittal, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Apeenasa is a first and foremost among the different types of Nasagata Roga described by Sushrut. There is vitiation of pitta and Kapha Dosha characterized by nasal obstruction, running nose, dryness of nose, anosmia and loss of taste and foul smell emanating from nasal cavity. This condition can be co-related with atrophic rhinitis because most of the signs and symptoms are similar. Apeenasa or atrophic rhinitis when reviewed in the texts has been an issue to be dealt with on a regular basis. The disease comprising of the association of Vata and Kapha doshas leading to a local Nasagata Samprapti causing lakshanas like Kshavathu (Sneezing), Nasavarodha (Congestion), Kalingadisrava (Running nose). Contemporary literary review indicates that same symptoms are found in allergic rhinitis which is induced by an IgE mediated inflammation of the nasal membrane. The chosen drug for conducting the study Kalingadi Taila and Shad Bindu Taila were considered as they are found to be effective in the treatment of the Kshavathu which is the predominant symptom of Apeenasa.